Rice-eel system combined with exogenous organic waste improves soil quality under nitrogen deficiency by regulating soil microbial community - Pei, Yanan; Yuan, Zihan; Lv, Weiguang; Qiu, Siyu; Xu, Chenglong; Zhu, Xianpu; Li, Shuangxi; Zhang, Juanqin; Bai, Naling; Zhang, Haiyun; Zhang, Hanlin (Frontiers in Microbiology, 2026)
BackgroundThe rice-eel system, a cultivation method integrating aquatic animals with rice, offers ecological and agronomic advantages, yet its long-term effects of substituting chemical fertilizers with straw or organic fertilizers on soil properties remain unclear.AimsThis study aimed to quantify the effects of organic waste substitutions within the rice-eel system on soil physicochemical properties and microbial communities.MethodsA 2016-established field experiment on sandy loam soil under rice-fallow rotation, and soil samples (0–20 cm and 20–40 cm depths) were taken in March 2025. The study included five treatments: conventional fertilization (100%) without eel (RT), conventional fertilization (100%) + eel (IRT), 70% chemical fertilization + eel (I70), 70% chemical fertilization + 30% straw + eel (IS), and 70% chemical fertilization + 30% organic fertilizer + eel (IO).ResultsThe system improved soil macroaggregate stability, with the strongest effects under IS and IO. Compared with RT, IS and IO significantly increased soil organic matter (SOM) by 16.04% on average, at 0–20 cm, and increased SOM and available phosphorus (AP) by 18.60 and 33.70%, respectively, at 20–40 cm. IS and IO significantly increased bacterial and fungal gene copies by an average of 64.95% (0–20 cm) and 76.20% (20–40 cm). The rice-eel system improved microbial diversity, reshaped community composition, and increased taxa such as Chloroflexi, Acidobacteriota, Pleosporales and Chytridiomycota which contribute to organic matter decomposition and aggregate formation. The relative abundance of microorganisms associated with aerobic respiration (cytochrome c pathway) increased, while functional pathways related to biosynthesis and degradation/utilization/assimilation were also strengthened.ConclusionThe rice-eel system—particularly IO—significantly improved fertility, aggregate stability, and microbial function. These findings indicate that the rice-eel system reduces reliance on chemical fertilizers while sustaining productivity, offering a practical strategy for ecological agriculture.